Development of a continuous process for α-thio-β-chloroacrylamide synthesis with enhanced control of a cascade transformation - Dennehy, Olga C.; Cacheux, Valérie M. Y.; Deadman, Benjamin J.; Lynch, Denis; Collins, Stuart G.; Moynihan, Humphrey A.; Maguire, Anita R. (Beilstein Journal of Organic Chemistry, 2016)
A continuous process strategy has been developed for the preparation of α-thio-β-chloroacrylamides, a class of highly versatile synthetic intermediates. Flow platforms to generate the α-chloroamide and α-thioamide precursors were successfully adopted, progressing from the previously employed batch chemistry, and in both instances afford a readily scalable methodology. The implementation of the key α-thio-β-chloroacrylamide casade as a continuous flow reaction on a multi-gram scale is described, while the tuneable nature of the cascade, facilitated by continuous processing, is highlighted by selective generation of established intermediates and byproducts.
Keywords: α-thio-β-chloroacrylamides; cascade reactions; flow chemistry